Negative Pressure Wound Therapy with Instillation for Periprosthetic Infection after Breast Reconstruction: A Systematic Review - Madeline J. O’Connor, BA; Kristin N. Huffman, BS; Kelly Ho, BS; Sammer Marzouk, MA; Rolando J. Casas Fuentes, BS; Kenneth L. Zhang, BS; Bradley A. Melnick, BS; Payton J. Sparks, BS; Raiven Harris, BA; Angelica V. Bartler, MS; Ashley Collinsworth, ScD, MPH; Leah Griffin, MS; et al. (Plastic and Reconstructive Surgery, Global Open)
Background:. Periprosthetic infection after breast reconstruction is not uncommon and can result in loss of the implant pocket and negative patient outcomes. Management of these infections typically involves removal of the prosthesis, treatment with antibiotics, and delayed reconstruction upon infection resolution. The impact of adjunctive use of negative pressure wound therapy with instillation and dwell (NPWTi-d) on breast pocket salvage rates, time to implant reinsertion, and related outcomes was examined. Methods:. A systematic literature search using PubMed, Cochrane, OVID, Scopus, and Embase was conducted to identify peer-reviewed articles written in English and published between January 2004 and April 2023 that examined NPWTi-d use in the breast pocket with a history of periprosthetic infection after breast reconstruction. Results:. Of the 1703 publications, 6 studies met inclusion criteria, representing 115 patients and 122 breasts. The overall breast pocket salvage rate with NPWTi-d across studies was approximately 92%. In the 6 studies that included prosthesis type and radiation history, overall salvage rates were 97.8% (45 of 46) for pockets containing implants and 93.8% (15 of 16) for pockets containing tissue expanders. Salvage rates were 85.7% (12 of 14) and 91.7% (53 of 58) for irradiated and nonirradiated breasts, respectively. Mean time to implant reinsertion ranged from 2.3 to 10.3 days. Conclusions:. In this review, antibiotic therapy along with adjunctive use of NPWTi-d for periprosthetic infections after breast reconstructions was associated with high rates of breast pocket salvage and reduced time to implant reinsertion. Larger prospective and randomized trials are needed to better understand and optimize the effectiveness of NPWTi-d in this population.